2017
DOI: 10.21517/0202-3822-2017-40-4-68-73
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar Properties of Disruptions on the T-10 Tokamak at Different Edge Safety Factor Values

Abstract: На токамаке Т-10 было обнаружено, что при срывах разряда по предельной плотности наблюдается зависимость длительности спада тока плазмы от величины запаса устойчивости на границе плазмы q a. Так, если q a до начала срыва имеет целое или полуцелое значение, то длительность спада тока плазмы составляет величину ~100-115 мс, тогда как при нецелых значениях q a длительность спада тока не превышает 15 мс. Медленный спад тока плазмы характеризуется большим количеством вспышек МГД-активности, которые, по-видимому, пр… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Related papers at the conference dealt both with further analyses of phenomena associated with disruptions in current experiments [94,95] and with the results of research addressing specific aspects of disruption mitigation physics and technology for ITER [96-100, 102, 103]. In a review of disruptions observed during the ITER-like wall phase of JET operation between 2011 and 2016, Gerasimov et al presented an analysis of rotating 3D equilibria observed following socalled asymmetric VDEs [94].…”
Section: Disruption Prevention Avoidance and Mitigationmentioning
confidence: 99%
“…Related papers at the conference dealt both with further analyses of phenomena associated with disruptions in current experiments [94,95] and with the results of research addressing specific aspects of disruption mitigation physics and technology for ITER [96-100, 102, 103]. In a review of disruptions observed during the ITER-like wall phase of JET operation between 2011 and 2016, Gerasimov et al presented an analysis of rotating 3D equilibria observed following socalled asymmetric VDEs [94].…”
Section: Disruption Prevention Avoidance and Mitigationmentioning
confidence: 99%